Dental age estimation employing CBCT scans enhanced with Mimics software: Comparison of two different approaches using pulp/tooth volumetric analysis - Asif, Muhammad Khan; Nambiar, Phrabhakaran; Mani, Shani Ann; Ibrahim, Norliza; Khan, Iqra Muhammad; Sukumaran, Prema (Elsevier, 2018)
The methods of dental age estimation and identification of unknown deceased individuals are evolving with the introduction of advanced innovative imaging technologies in forensic investigations. However, assessing small structures like root canal volumes can be challenging in spite of using highly advanced technology. The aim of the study was to investigate which amongst the two methods of volumetric analysis of maxillary central incisors displayed higher strength of correlation between chronological age and pulp/tooth volume ratio for Malaysian adults. Volumetric analysis of pulp cavity/tooth ratio was employed in Method 1 and pulp chamber/crown ratio (up to cemento-enamel junction) was analysed in Method 2. The images were acquired employing CBCT scans and enhanced by manipulating them with the Mimics software. These scans belonged to 56 males and 54 females and their ages ranged from 16 to 65 years. Pearson correlation and regression analysis indicated that both methods used for volumetric measurements had strong correlation between chronological age and pulp/tooth volume ratio. However, Method 2 gave higher coefficient of determination value (R2 = 0.78) when compared to Method 1 (R2 = 0.64). Moreover, manipulation in Method 2 was less time consuming and revealed higher inter-examiner reliability (0.982) as no manual intervention during ‘multiple slice editing phase’ of the software was required. In conclusion, this study showed that volumetric analysis of pulp cavity/tooth ratio is a valuable gender independent technique and the Method 2 regression equation should be recommended for dental age estimation.